Effects of toll-like receptor-4 gene polymorphisms on soluble P-selectin and von Willebrand factor levels in hypercholesterolemic patients - Nisio, Marcello Di; Febbo, Concetta Di; Moretta, Valeria; Guglielmi, Maria Domenica; Stuppia, Liborio; Cuccurullo, Franco; Porreca, Ettore (Thrombosis and Haemostasis, 2007)
Toll-like receptor-4 (TLR-4) gene polymorphisms have been associated with a lower risk of atherosclerosis. High levels of soluble P-selectin (sP-selectin) and von Willebrand factor predict an increased risk for cardiovascular events and correlate to atherosclerotic risk factors. The relationship between these markers and TLR-4 gene polymorphisms was evaluated in a cohort of consecutive hypercholesterolemic outpatients. TLR-4 gene polymorphisms were detected in 48 out of 330 (14%) patients with hypercholesterolemia. Lipid and inflammatory markers, sP-selectin and von Willebrand were evaluated in carriers and in 96 (ratio 2:1 to cases) age- and sex-matched TLR-4 wild-type patients randomly selected from the same population. A cohort of normocholesterolemic outpatients (n=262) served as the control group.sP-selectin was sensibly lower in carriers of TLR-4 variants as compared to wild-types and controls (89 ng/ ml vs. 162 ng/ml and 163 ng/dl, respectively, p=0.0001). Similarly, carriers showed lower von Willebrand factor values (683 mU/ ml) than wild-types (910 mU/ml; p=0.001). In multivariate analysis, TLR-4 gene polymorphisms were positively associated with sP-selectin, whereas the relationship with von Willebrand factor was no longer significant. HMG-CoA reductase inhibitors reduced sP-selectin and von Willebrand factor levels independently of TLR-4 gene variants. Plasma concentrations of these markers, however, remained lower in carriers of TLR-4 gene polymorphisms even after cholesterol lowering. In conclusion, carriership of Asp299 andThr399IleTLR-4 gene polymorphisms is associated with lower levels of sP-selectin and von Willebrand factor among hypercholesterolemic patients. While the underlying mechanisms remain to be investigated, such an association may indicate a protective effect of TLR-4 variants for atherosclerosis.
Keywords: Toll-like receptor; gene polymorphism; P-selectin; von Willebrand factor; hypercholesterolemia